Role of physical and engineering properties of rice (Oryza sativa) cultivars for designing of precision planter - RAJAIAH, P; MANI, INDRA; KUMAR, ADARSH; LANDE, SATISH DEVARAM; SINGH, ASHOK KUMAR (The Indian Journal of Agricultural Sciences, 2015)
The paper describes the effect of physical and engineering properties of five rice (Oryza sativa L.) cultivars, viz. Pusa 1121, Pusa 44, BPT 5205, MTU 7209 and MTU 1010 on the design parameters of precision planter for direct sowing of rice seeds in drylands. The properties were determined in three conditions of seeds, viz. dry condition, 1- day soaking and two day soaking condition. In all the five selected varieties, no significant difference in length was found between dry and soaked seed, while breadth and thickness of the seeds were found slight increase in all varieties. It was observed that the grain length varied from 7.32±0.61 to 13.79±0.93 mm, breadth 2.16±0.21 to 2.58±0.06 mm, sphericity, 43.66±2.45 to 30.56±3.49, 1000 grain-weight 14.37 to 32.6 g, angle of repose 25.25 to 33.68° and bulk density 524.6 to 667.56 kg/m3.The observed values can be used to fabricate the seed metering cells for different varieties with cell diameter ranging from 10 mm to 14 mm. Thickness and cell diameters of the seed metering discs were designed in reference to the maximum breadth and length. Based on the results, it can be revealed that flow rate from the hopper can be affected due to angle of repose and coefficient of friction for rice grains. Thus, to design the hopper the average values of angle of repose and coefficient of friction can be taken. The highest angle of repose observed in PUSA 1121 can be used to have a seed hopper slope of 35° to ensure free flow of seed. The coefficient of friction in all the selected varieties was less with mild steel as compared to galvanized-iron and wood surfaces. It was concluded that a minimum angle of 30°and a plate thickness of 4 mm can be used to design a hopper by selecting the low friction mild steel sheet. The measured bulk density and size values can be used to design a hopper of required capacity and seed metering plate cell size for required number of seeds/hill.